Burn out: Ukrainian realities (based on some medical professions) - Chaban Олег; Salnikova Аліна (Psychosomatic Medicine and General Practice, 2020)
Background: The spread of burnout syndrome contributes to our era - the time of achievement, consumption, new materialism, entertainment and enjoyment of life. This is the time when we exploit ourselves and allow ourselves to exploit. But you need to keep in mind that emotional burnout occurs in those professions where there is not only a heavy load but also a constantly acting chronic stress. This article discusses the “Burn out” problem in the context of the medical profession in Ukraine. Results: After a survey among doctors, we saw some features of “Burn out” in different regions of Ukraine and their phenomenological content. There was a survey among different medical specializations, which allowed us to see the difference between the emotional burnout of endocrinologists, cardiologists, oncologists, and gynecologists. Methods: “Questionnaire for the identification of burnout syndrome” O. Chaban Conclusion: emotional burnout is a process in which the doctor himself actively participates and, if the signs of “Burn out” are detected at the beginning of the process, he has the opportunity to make changes in his life. Comparing the facts of the study, one can imagine the Ukrainian doctor as a certain robot who voluntarily sacrifices himself, but receives almost nothing for this. The sacrificial position of a Ukrainian doctor is probably due to living in certain personal and social myths.